Decolorization of waste water from reactive dyes - (:unkn) unknown (My University, 1995)
Effluent from using eleven reactive dyes having different chromophores and different reactive groups have been exposed to different pH values in daylight and in the dark. Laser radiation, ultraviolet radiation, ultraviolet radiation in combination with hydrogen peroxide at alkali pH and ultraviolet radiation combined with hydrogen peroxide at pH = 1 were used. It was noted that decolorization of dyeing effluent is faster at pH = 2 than under any other pH conditions. It is faster in the daylight than in the dark, the best result being obtained with ultraviolet radiation combined with hydrogen peroxide at pH = 1.0. The last method is advisable because it is environmentally friendly.